Design Management as an Effective User‐Centric Management Tool for Organizations. (6th August 2021) - Ozkan, Gulay
Abstract : Design management may be the way to make sure that the user perspective or, in other words, human data is prioritized and not lost within an organization in parallel to the project management functions. Design's valuable tools and perspectives help keep the user at the center of projects and bring success to even the most complex working environment.